ANALISIS PENGARUH CORPORATE GOVERNANCE, RELATED PARTY TRANSACTION, KONSENTRASI KEPEMILIKAN DAN NILAI PERUSAHAAN TERHADAP TINGKAT ASIMETRI INFORMASI - Hermi Hermi; Emayanti Christina Hutabarat (Jurnal Akuntansi Trisakti, 2017)
This research examines to analyze the impact of Corporate Governance, Related Party Transaction, Ownership Concentration, Corporate Value  On The Level of Asymmetric Information .The results of this study indicate that (1) Corporate governance is no negative influence on to increase information asymmetry. (2) Related party transaction is no positive influence to increase information asymmetry(3) Ownership concentration is  positive influence to increase information asymmetry (4)The corporate value is no negative influence to increase information asymmetry